Aqueous humour cytokines profiles in eyes with Coats disease and the association with the severity of the disease - Tingyi Liang; Yu Xu; Xiuyu Zhu; Xiang Zhang; Jing Li; Peiquan Zhao (BMC Ophthalmology, 2020)
Abstract Background To investigate aqueous humour (AH) cytokine profiles in eyes with Coats disease and analyze the association between cytokine concentrations and the severity of the disease. Methods The study included 36 patients (36 eyes) with Coats disease and 15 control patients (15 eyes) with congenital cataract. AH samples were obtained preoperatively and the concentrations of 22 different cytokines were measured through Cytometric Bead Array technology. Clinical characteristics of Coats disease, including the extent of retinal exudation and exudative retinal detachment (ERD), were recorded for analysis. Results The concentrations of 8 cytokines (VEGF, IL-6, IL-8, MCP-1, MIP-1α, IP-10, VCAM-1 and ICAM-1) were significantly higher in the Coats disease group than in the control group (all P < 0.002). Except for VCAM-1 and ICAM-1, the concentration of the other cytokines listed above showed a significant increase from stage 2 to stage 3 (all P < 0.05). Meanwhile, the concentrations of VEGF, IL-8, MCP-1 and MIP-1α showed a significant and positive association with the extent of retinal exudation and ERD (all r > 0.4, P < 0.05). Among these, IL-8 showed a strong association with the extent of retinal exudation and ERD (all r > 0.7, P < 0.001). The concentrations of IL-1α, IL-1β, IL-2, IL-4, IL-5, IL-10, IL-12, Fractalkine, RANTES, G-CSF and GM-CSF were very low in both groups. Conclusions Various cytokines in the AH, including elevated VEGF, IL-6, IL-8, MCP-1, MIP-1α, IP-10, VCAM-1 and ICAM-1, may be involved in the pathogenesis and progression of Coats disease. Increasing severity of Coats disease is significantly associated with the AH concentrations of VEGF, IL-8, MCP-1 and MIP-1α. Further clinical treatment aimed to reduce vascular leakage and antagonize neovascularization and inflammation may be useful in preventing the progression of Coats disease.